Pengaruh Kualitas Konten Instagram @seputarsemarang terhadap Pemenuhan Kebutuhan Informasi Warga Semarang - Dhavin Shaaka Abiyoga; Ami Saptiyono (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study's objective is to examine the extent to which the content shared on the Instagram account @seputarsemarang impacts the satisfaction of information needs among residents of Semarang. The central inquiry focuses on whether the quality of content significantly correlates with the degree to which various dimensions of information needs are met, encompassing cognitive, affective, personal integration, social integration, and escapism-related aspects. To assess content quality, four key indicators were utilized: accuracy, comprehensiveness, relevance, and timeliness. Employing a quantitative approach within an associative research framework, this study utilized a structured questionnaire featuring close-ended items on a four-point Likert scale, administered to a selected sample of 100 followers of the @seputarsemarang account. The analytical procedures encompassed assessments of validity and reliability, alongside statistical techniques including t-test, cross-tabulation, Chi-Square analysis, and Cramer’s V measurement. Findings reveal that the obtained t-value of 17.094 significantly surpasses the critical t-table value of 1.290 at a significance threshold of <0.001. Additionally, the Cramer’s V coefficient of 0.591 signifies a moderately strong correlation. These outcomes reinforce the Uses and Effects theory, underscoring the influential role of media content in shaping audience perceptions and experiences. The study emphasizes the importance of local social media as a reliable source of information for urban communities and contributes empirically to the development of social media and communication studies.